Isolation of a Halophilic, Bacteriorhodopsin-producing Archaeon, Haloferax larsenii RG3D.1 from the Rocky Beach of Malvan, West Coast of India. Issue 3 (16th March 2017) - Kanekar, Pradnya P.; Kulkarni, Snehal O.; Dhakephalkar, Prashant K.; Kulkarni, Kantimati G.; Saxena, Neha
ABSTRACT: Haloarchaea live in saline environments and require salt for their growth. The present study reports on the isolation of a haloarchaeal strain RG3D.1 identified as Haloferax larsenii using Sehgal and Gibbons medium with 3.42 M NaCl, from Rock Garden at Malvan in the West Coast of India. The rock type of Malvan Coast is correlated based on geological setting with the basal member of the Bababudan group placed at 2728 ± 102 million years ago (Ma). The haloarchaeal strain produced bacteriorhodopsin (BR) (0.137 g l −1 ) and generated electric potential of 49.2 mV when exposed to sunlight. Thus, this is the first report on the isolation of a haloarchaeon, Haloferax larsenii, from red rocky substrate and production of BR.